Empathy, group identity, and the mechanisms of exclusion: an investigation into the limits of empathy - Fuchs, Thomas (Topoi, 2019)
There is a conspicuous tendency of humans to experience empathy and sympathy preferentially towards members of their own group, whereas empathetic feelings towards outgroup members or strangers are often reduced or even missing. This may culminate in a “dissociation of empathy”: a historical example are the cases of Nazi perpetrators who behaved as compassionate family men on the one hand, yet committed crimes of utter cruelty against Jews on the other. The paper aims at explaining such phenomena and at determining the limits of empathy. To this purpose, it first distinguishes between two levels of empathy, namely primary or intercorporeal and extended or higher-level empathy. It then investigates the mutual interconnection of empathy and recognition, which may be regarded as a principle of extending empathy to others regardless of whether they belong to one’s own group or not. However, this principle is in conflict with ingroup conformism and outgroup biases that hamper the universal extension of empathy. Thus, a denial of recognition and exclusion of others from one’s ingroup usually results in a withdrawal or lack of extended empathy which then influences primary empathy as well. On this basis, and using the historical example of mass executions during the Holocaust, the paper investigates the mechanisms of exclusion which may lead to a withdrawal of recognition and finally to a dissociation of empathy.